Asian mobilities and state governance at the geographic margins: Geopolitics and oil tales from Karachi to Taftan. (June 2016) - Anwar, Nausheen H
This article's central concern is to consider the geographic 'margins' in relationship to state governance in Pakistan. In doing so, it gestures toward wider theoretical lessons that can be drawn through ethnographic explorations of Karachi's periphery and of Pak–Iran border towns such as Taftan located in the province of Baluchistan. Central to the discussion is the idea of mobility. The article considers three different types of mobility across Pakistan set in the broader context of Central-South Asian historical connectivities. First is the movement of 'illicit' commodities such as diesel across Pakistan's border with Iran, forced migrations across Pakistan's northwest region in relationship to the war on terror, and finally, the role of road networks in mediating mobilities: in short, mobility is considered across commodities, displacement, and infrastructure. How do these Asian mobilities shed light on the state? The idea of the margins is particularly helpful in theorizing the role of the state. These are liminal zones of creativity where money can be made but are also fraught with risk and conflict because they are beyond the reach of formal governance. The article opens with a history of Karachi and its surrounding regions, including its colonial past and the making of the Indus River which has always been of geopolitical importance. It then moves to a discussion of the diesel trade in the region. The flow of Iranian diesel into Karachi via towns like Taftan in Baluchistan represents a mingling of actors—mercenaries, drug traffickers, and diesel merchants—and the Pakistani state's failure to sufficiently control this flow, which has become a lucrative business for some and a lifeline for others across Baluchistan and in Karachi's periphery. The article then prefaces the role of infrastructure and its relationship with modernity and the Pakistani state. In conclusion, the article argues the margins should not be seen as being 'outside' of the nation-state or as some kind of 'exceptional' space. Rather they should be understood as constitutive of the state's very 'inside' precisely because they are beyond its reach.